Crônica: um retrato bem-humorado do tempo presente - Chapola, Ricardo Antonio Casadei (2016)
This thesis's goal is to show how the hybrid character of chronic accredits the Gender being Another possibility present's time narrative representation. Being linked to literature NOT necessarily oblige the chronic to tell just lies. Its relationship with fiction Also Brings gains in other aspects, especially on its language: lighter, more loose. The language of humor, by the way, that in chronic acquires other papers in addition of simply fun anyone. Its an important ingredient on this possibility portrait of time and space.